Analisis Persepsi Praktisi Akuntansi terhadap Implementasi PSAK 74 pada Perusahaan Asuransi di Indonesia - Prayoga Jati Aditama; Nurhastuty Kesumo Wardhani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The transition from PSAK 62 to PSAK 74 marks a paradigm shift in financial reporting within Indonesia’s insurance industry, emphasizing transparency, present value measurement, and systematic profit recognition. The urgency of this research stems from the complexity of implementing the new standard and the varying levels of preparedness among insurance companies. This study aims to analyze accounting practitioners’ perceptions of PSAK 74 implementation, exploring organizational readiness, transitional challenges, the impact on financial statements, and perceived benefits. The main research question addresses how practitioners respond to the standard change and what factors influence successful implementation. This research employs a qualitative approach using an exploratory case study design. Data were collected through in-depth interviews with practitioners from several insurance companies in Indonesia and analyzed thematically to identify patterns, insights, and barriers during the implementation process. The findings reveal that most companies demonstrate strategic readiness through roadmap development and training but continue to face challenges in information systems and human resource capabilities. PSAK 74 is perceived to significantly affect financial reporting structures and promote a shift in organizational culture toward cross-functional collaboration. These findings contribute to a deeper understanding of the dynamics of IFRS-based standard implementation in the insurance sector and highlight the need for interdisciplinary approaches and regulatory support throughout the transition. The study concludes that successful PSAK 74 implementation depends on the synergy between technical readiness, internal coordination, and conceptual understanding of the standard. It also recommends holistic training, IT system upgrades, and further research using quantitative methods to enhance the breadth and validity of future findings.